2020
DOI: 10.1177/1179557320941478
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Depression Are Associated With More Anxiety in ME/CFS: A Cross-Sectional Cohort Study Between Norway and Spain

Abstract: Objectives: Lasting, unexplained and high levels of pain may cause anxiety in patients with chronic fatigue syndrome. The objectives of the current study were to test assumptions of the association between pain and anxiety in patients diagnosed with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and to clarify the role of depression in this relationship. Methods: Data were collected from 664 participants (age 18-65 years) with 133 ME/CFS patients and 201 healthy controls from Norway and 330 CFS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, the comparison rates used were also assessed during the COVID-19 pandemic, though one year earlier (April–May 2020) [28]. Similar to other patient populations, depression and anxiety frequently co-occurred in QFS patients; over half of the patients in our study who had a score indicative of depression also had a score indicative of anxiety [31].…”
Section: Discussionmentioning
confidence: 96%
“…However, the comparison rates used were also assessed during the COVID-19 pandemic, though one year earlier (April–May 2020) [28]. Similar to other patient populations, depression and anxiety frequently co-occurred in QFS patients; over half of the patients in our study who had a score indicative of depression also had a score indicative of anxiety [31].…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, other than fatigue, pain has been identified as the most troublesome ME/CFS symptom, with 65% of severely ill patients identifying pain as the top three most troublesome [ 14 ]. Among people with ME/CFS, research found that pain was associated with reduced functioning and quality of life [ 41 ]; if accompanied with depression, pain was also associated with anxiety [ 42 ]. Several measures have been used in clinical settings to evaluate ME/CFS pain [ 43 – 49 ]; however, such measures often focus on the frequency and severity of pain [ 37 ], while the specific consequences of pain on daily functioning and interference with life have not been fully assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic pain among adults seen in the primary care setting ranged between 10% and 15% (Nahin, 2015). Mood disorders, including depression and anxiety disorders, are also common health issues in primary care settings (Gold et al, 2020;Strand, Castro-Marrero, Helland, Alegre, & Mengshoel, 2020). Up to 14% of patients seen in primary care have estimated to have depression (Gonzalez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%